Influence of Sargassum POC and Nano Bubble Technology on Hydroponic Pakcoy (Brassica rapa L.) Quality - Afrilisia, Lora; Fevria, Resti; Vauzia, Vauzia; Razak, Abdul (Jurnal Biologi Tropis, 2025)
The decline in vegetable production is caused by the conversion of agricultural land into residential areas which results in a reduction in agricultural land area. To overcome this problem, the hydroponic system is one of the alternative solutions used to replace lost agricultural land. The purpose of the study was to determine the effect of providing liquid organic fertilizer (POC) derived from (Sargassum sp.) with nano bubble technology on the quality of pakchoy (Brassica rapa L.) plants in hydroponic cultivation. The research method used a Completely Randomized Design (CRD) with five treatments. Data were analyzed using the ANOVA test and Duncan's test. The results showed that the P2 and P3 treatments were significantly different in increasing plant height with the highest average of 23.4 cm and the lowest P5 of 13.56 cm. Likewise, P3 produces the most optimal average number of leaves and overall plant quality, the cause is the availability of balanced nutrients. Nano bubble technology increases the efficiency of nutrient absorption and reduces sedimentation in the wick hydroponic system. The conclusion is that the combination of AB Mix and POC Nano is able to optimize the growth and quality of pakchoy plants in the hydroponic system, showing the potential for sustainable agriculture using innovative fertilizer technology.